1997
DOI: 10.1002/cjce.5450750418
|View full text |Cite
|
Sign up to set email alerts
|

Bubble drag in contaminated non‐newtonian solutions

Abstract: The motion of a bubble in an infinite fluid is examined in the case where the surrounding fluid is nowNewtonian and contains impurities. An expression is developed for the drag force as a function of the shear-thinning character as well as of the concentration of surfactant of the fluid. The obtained expression for the drag force correlates quite nicely with experimental data for small bubbles.On examine le deplacement d'une bulle dans un fluide infini dans le cas ou le fluide environnant est non newtonien et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The average value of the surface tension was 0.063 N/m. These results agree well with previously published data 8 and show that the surfactant concentrations used are well below the critical micelle concentration.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The average value of the surface tension was 0.063 N/m. These results agree well with previously published data 8 and show that the surfactant concentrations used are well below the critical micelle concentration.…”
Section: Resultssupporting
confidence: 93%
“…[4][5][6] It has been shown that, in general, bubbles rising in pure liquids, containing no surfactants, have higher terminal velocities than bubbles rising in surfactant-containing liquids. [7][8][9][10] When gas bubbles are released into a solution containing a surfactant, the latter will accumulate on the liquid-gas interface created by the bubble and solution. They found that the presence of a surfactant would decrease the bubble velocity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Rodrigue et al 27 experimentally investigated the rising velocity of contaminated bubbles in Carreau model fluids and presented a correlation. Subsequently, they 28 employed the standard perturbation technique to obtain an approximate expression for drag of a contaminated bubble in Carreau model fluids in the limit of small Carreau numbers and Reynolds numbers, i.e., for weak shear-thinning and inertial conditions. In a later study, they 29 employed a thermodynamic approach (which assumes linear deviation in the surface tension from the equilibrium value) and a physical approximation (based on geometry and boundary conditions) in the limit of small Reynolds numbers.…”
Section: Previous Workmentioning
confidence: 99%
“…Rodrigue et al (1996Rodrigue et al ( , 1997 experimentally and theoretically investigated the rising velocity of contaminated bubbles in Carreau model non-Newtonian fluids in the limit of small Carreau numbers. By the use of a thermodynamic approach and a physical approximation, Rodrigue et al (1999) further studied the rise of bubbles in power-law and Carreau model type non-Newtonian fluids in the limit of small Reynolds number.…”
Section: Previous Workmentioning
confidence: 99%